RP-US FTA: Trade Remedies, Competition Policy and Government Procurement - Atty. Jeremy Gatdula; Ever Higuit; Rafael Madarang (Philippine Institute for Development Studies (PIDS), 2006)
This paper was designed to provide a policy guide in the formulation of the countrys position for RP-US FTA negotiations. After sieving through the relevant treaties and legislation in both the US and the Philippines, it was concluded that the implementation of treaty commitments in trade remedies, competition policy and government procurement in an FTA scenario with the US would be a highly technical endeavor for which the Philippines may not yet have the sufficient competencies to thoroughly comply. Thus, the provisions that shall come out of the final negotiations, if the same do push through, should not bind the Philippines to specific treaty commitments that, in the long run, the country may not be able to enforce and properly abide by. Also, these possible treaty commitments should not exceed the countrys existing international agreements and domestic laws so as not to burden the Philippines with another set of compliance requirements-which may divert attention from the primary FTA objective of paving wider opportunities for Philippine products to enter the US market and gearing Philippine industries towards better competitiveness.
Keywords: 330; World Trade Organization; competition policy; government procurement; safeguard measures; anti-dumping; countervailing measures; free trade agreements (FTAs); Internationale Wirtschaftsbeziehungen; Freihandelszone; Außenwirtschaftspolitik; Antidumping; Wettbewerbspolitik; Öffentlicher Auftrag; Philippinen; USA